日本人英語学習者の学習活動に対する印象についての調査 : その縦断的研究 - 木村, 裕三 (全国英語教育学会紀要, 1998)
This paper reports on a longitudinal study which examined how Japanese EFL learners have changed their attitudes towards communicative and non-communicative activities after one year. A 1-5 Likert scale questionnaire containing ll examples of activities of English lessons were replicated to the same subjects in Kimura (1995) as well as to newly participating subjects. Compared with the results from one year before, the present survey observed significant differences of impressions in both high school teachers and high school students. The results also indicated interesting discrepancies among teachers, high school students and university students.